The Impact of Board Gender Diversity on Firm’s Credit Ratings - Iryanti, Ika (Management Analysis Journal, 2021)
Motivated by the agency theory and resource dependence theory, this study aims to examine the level of gender diversity on credit rating. This study uses a panel data sample of firms listed in BEI for the years 2014 to 2019. This study enlarge the literature by serve evidence on the role of gender diversity on firm’s credit rating that was essence neglected by the previous studies. This study contributes practically and theoretically to the existing credit rating literature. This finding shows board gender diversity is positively not significantly correlated with credit ratings. The evidence was contrary to the assumption that firms with increased board gender diversity are associated with fewer agency problems and information asymmetry, which can positively affect credit rating.